2017
DOI: 10.1038/srep42833
|View full text |Cite
|
Sign up to set email alerts
|

Control of terahertz nonlinear transmission with electrically gated graphene metadevices

Abstract: Graphene, which is a two-dimensional crystal of carbon atoms arranged in a hexagonal lattice, has attracted a great amount of attention due to its outstanding mechanical, thermal and electronic properties. Moreover, graphene shows an exceptionally strong tunable light-matter interaction that depends on the Fermi level - a function of chemical doping and external gate voltage - and the electromagnetic resonance provided by intentionally engineered structures. In the optical regime, the nonlinearities of graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Additionally, engineering efforts aimed at achieving a longer interaction length, instead of a deep-subwavelength interaction length of the photoconductive layer, may significantly improve the efficiency. Furthermore, instead of doped GaAs, other materials with high nonlinearities, such as graphene, [18,21,22] may also be utilized for electric-field-induced nonlinear processes at THz frequencies. Through these improvements and investigations, the electric-field-induced nonlinear process will present a new route for developing nonlinear optical devices in the THz spectral range, thereby further enhancing the capabilities of THz science and technology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, engineering efforts aimed at achieving a longer interaction length, instead of a deep-subwavelength interaction length of the photoconductive layer, may significantly improve the efficiency. Furthermore, instead of doped GaAs, other materials with high nonlinearities, such as graphene, [18,21,22] may also be utilized for electric-field-induced nonlinear processes at THz frequencies. Through these improvements and investigations, the electric-field-induced nonlinear process will present a new route for developing nonlinear optical devices in the THz spectral range, thereby further enhancing the capabilities of THz science and technology.…”
Section: Resultsmentioning
confidence: 99%
“…sources of THz optical nonlinearities, one of the most promising is the nonlinear response of carriers in semiconductors and graphene to an intense THz field. [13][14][15][16][17][18][19][20][21][22] This nonlinear behavior is attributed to energydependent scattering during carrier drift transport. By utilizing the highly nonlinear response of carriers, various nonlinear optical phenomena have been observed at THz frequencies, such as absorption bleaching, [13][14][15][16][17][18] self-phase modulation, [19] and harmonic generation.…”
Section: Doi: 101002/adom202000359mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent progress in THz graphene research has shown that even at modest fields on the order of tens of kV/cm a field dependent increase in transmission can be observed due to a nonlinear response of the excited carriers [8,[9][10][11][12][13][14]. With high field THz setups and high mobility large-area graphene samples more commonly available, the study of nonlinear THz properties has intensified significantly.…”
Section: Introductionmentioning
confidence: 99%